FORMULATION AND EVALUATION OF ISORHAMNETIN LOADED POLY LACTIC-CO-GLYCOLIC ACID NANOPARTICLES - Settu, Kandakumar; Vaiyapuri, Manju (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The aim of the present study was formulation and evaluation of isorhamnetin loaded poly lactic-co-glycolic acid (PLGA) polymeric nanoparticles (NPs). Methods: The present study was designed to incorporate the isorhamnetin in PLGA formulation by double emulsion solvent evaporation method, which offers a dynamic and flexible technology for enhancing drug solubility due to their biphasic characteristic, variety in design, composition and assembly. Synthesized isorhamnetin-PLGA NPs were characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and particle size analyzer. We tested the efficacy of isorhamnetin-PLGA NPs in HepG2 cell lines. Results: From the FTIR result, we concluded that -C-N-, -C=C-, N-H, C-N, N-O, O-H, and C-H are the functional groups present in isorhamnetin-PLGA NPs, SEM image shows spherical shape of particles. The particle size analysis result shows 255-342 nm range of particles. Isorhamnetin-PLGA NPs significantly enhanced (p<0.05) the antiproliferative effect when compared to the plain drug. Conclusion: This study concluded that the newly formulated NP drug delivery systems of isorhamnetin provided an insight into the therapeutic effectiveness of the designed formulation for the treatment of chemotherapy.